Lake ice phenology in the Northern Hemisphere extracted from SMMR, SSM/I and SSMIS data from 1979 to 2021 - Yu Cai; Claude R Duguay; Chang-Qing Ke (PANGAEA, 2022)
This dataset contains ice phenology for 56 lakes in the Northern Hemisphere from 1979 to 2021. The ice phenology was extracted from 3.125 km 37 GHz H-polarized evening brightness temperature data from Scanning Multi-channel Microwave Radiometer (SMMR), Special Sensor Microwave Image (SSM/I) and Special Sensor Microwave Imager/Sounder (SSMIS) data in the Calibrated Enhanced Resolution Brightness Temperature (CETB) dataset.